Exigências de energia para mantença e ganho de peso de fêmeas Santa Inês e equações para predição do peso de carcaça, peso de corpo vazio, ganho de peso de corpo vazio e energia retida - Brito Neto, Antonio de Sousa (2024)
The objective of the present study was to evaluate body composition and estimate energy requirements for maintenance and weight gain of Santa Ines females at different ages, and to develop equations to predict carcass weight (CW), empty body weight (EBW), empty body weight gain (EBWG) and retained energy (RE) of hair sheep in a multi-study approach. Forty Santa Inês females with an average initial body weight (BW) of 16.27 ± 1.44 kg and approximately 150 days of age were used. Four females were slaughtered on the first day of the experimental period, constituting the reference group, which was used to estimate the initial EBW and initial body composition of the experimental animals. The remaining 36 females were distributed in a completely randomized design in a factorial arrangement (3 × 3) with 3 concentrate levels and 3 slaughter ages. For the multi-study approach, a dataset with 569 sheep derived from sixteen studies was used, with records of intact males, castrated males and females from different racial groups of hair sheep. The intercept (P = 0.190) and slope (P = 0.134) of the exponential relationship between heat production and metabolizable energy intake were not influenced by age, with net energy (NEm) and metabolizable energy (MEm) for maintenance being estimated at 0.077 and 0.122 Mcal/kg0.75 EBW/day, respectively. ER was regressed as a function of EBW0.75 and EBWG to estimate net energy for gain (NEg), and no effect of age was observed on the intercept (P = 0.521) and slope (P = 0.520) of this relationship, a general equation was obtained: NEg = 0.4489 (±0.1411) × EBW0.75 × EBWG1.0284 (±0.1399). Santa Inês females gaining 150 g/day and with BW varying from 10 to 40 kg require 0.203 to 0.698 Mcal/day of NEg, respectively. To predict CW, EBW, EBWG and RE, the following equations were generated and validated: CW = -0.2347 (±1.1358) + 0.4858 (±0.0387) × Fasting BW; EBW = 1.3677 (±0.5472) + 1.6812 (±0.0210) × CW; EBWG = 0.0046 (±0.0026) + 1.6797 (±0.0758) × Carcass gain (CG); Intact males: RE = 0.3463 (±0.0657) × EBW0.75 × CG0.7973 (±0.0400); Castrated males: RE = 0.3638 (±0.0699) × EBW0.75 × CG0.7973 (±0.0400); Females: RE = 0.4368 (±0.0739) × EBW0.75 × CG0.7973 (±0.0400). The energy requirements for maintenance and weight gain in Santa Inês females do not vary between 200 and 330 days of age. The equations generated to predict carcass weight, empty body weight, empty body weight gain and retained energy will provide support for feeding Systems and meat production.